Bioenergía, una alternativa energética sustentable para Colombia. Aplicación del Concepto Integrado de Sostenibilidad (ICoS) (2019)
Abstract: The production of energy from biomass has taken relevance in the world in recent years. The growth of alternatives for energy use of residual biomass has generated interest in evaluating the sustainability of these projects. This paper reviews some of the sustainability evaluation methodologies used and, through the Integrated Sustainability Concept (ICoS), develops a methodology to apply this evaluation scheme in Bioenergy projects in Colombia. The ICoS developed includes criteria and indicators for the evaluation of the performance of Bioenergy projects in: waste management, energy performance, energy equity, climate change, among others. This scheme is applied to evaluate the performance of the Guabal landfill in the municipality of Yotoco in three scenarios: uncontrolled methane burning, controlled methane burning and generation of energy from biogas, finding that the last scenario is what allows better performance in the evaluation of sustainability.